2007
DOI: 10.1161/circulationaha.107.688044
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Anabolic Deficiency in Men With Chronic Heart Failure: Prevalence and Detrimental Impact on Survival”

Abstract: We thank Pascual-Figal et al for their insightful comments on our article, 1 in which we have demonstrated that multiple anabolic deficiency is common in men with stable systolic chronic heart failure (CHF) and adversely relates to long-term survival.Spironolactone interacts with androgen steroid synthesis and metabolism; it is not clear whether a reduction in serum levels of sex steroids in men is a consequence of spironolactone therapy. 2 Of 208 CHF men in our study, 53 (25.5%) were treated with spironolacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
3
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(208 citation statements)
references
References 4 publications
8
191
3
6
Order By: Relevance
“…...Impaired anabolic metabolism may be a generalized phenomenon seen in the course of CHF that begins at an early stage of disease and accelerates the endocrine changes that normally occur in the course of male aging." 49 In contrast, in another study, low testosterone correlated with worse prognosis, but on multivariate analysis of confounders, the association vanished. The authors concluded that low testosterone might be a result of heart failure, and questioned testosterone deficiency as a causative agent of heart failure.…”
Section: Androgen Administration and Cardiac Function In Menmentioning
confidence: 87%
See 1 more Smart Citation
“…...Impaired anabolic metabolism may be a generalized phenomenon seen in the course of CHF that begins at an early stage of disease and accelerates the endocrine changes that normally occur in the course of male aging." 49 In contrast, in another study, low testosterone correlated with worse prognosis, but on multivariate analysis of confounders, the association vanished. The authors concluded that low testosterone might be a result of heart failure, and questioned testosterone deficiency as a causative agent of heart failure.…”
Section: Androgen Administration and Cardiac Function In Menmentioning
confidence: 87%
“…Low testosterone has been associated with heart failure, but impaired androgen metabolism has not been proven to be a cause of heart failure. 48,49 In contrast, consistent evidence from a number of small randomized studies have shown that testosterone therapy for heart failure in men improves exercise tolerance, cardiorespiratory function, and functional status, but does not appear to directly improve left ventricular function. [50][51][52][53] Selected effects of androgens on cardiac function are represented in Figure 1.…”
Section: Summary Of Effects Of Androgens and Adt On Heart Failurementioning
confidence: 99%
“…Of note, this prevalence is in the same order of magnitude as described for patients with heart failure (ie, 20%-30%) [10,11]. In addition, the increase in SHBG levels and the tendency toward lower levels of albumin in patients with heart failure may result in relatively lower levels of bioavailable or free testosterone compared to healthy patients of similar age [12,13].…”
Section: Diagnosis Of Androgen Deficiencymentioning
confidence: 83%
“…In a prospective cohort study of 206 middle-aged men with chronic systolic heart failure, 36% died during a median follow-up of 3.1 years. Higher total and free testosterone levels independently predicted better survival after adjustment in multivariable analysis [12]. In a similar cohort of 193 middle-aged men with chronic heart failure followed for 2.3 years (28% mortality), lower levels of free, but not total testosterone were associated with higher mortality risk in analyses adjusting for age and New York Heart Association (NYHA) class.…”
Section: Modification Of Risk By Androgens In Heart Failurementioning
confidence: 95%
“…Thus important aspects of illness, such as pain and suffering [39] as well as social isolation [40] may contribute to the excess cost. Multisystem disorders that are widely prevalent in aging, such as the metabolic syndrome, frailty syndrome, and chronic heart failure are more significantly associated with endocrine disruptors of the GH/IGF-I axis [41].…”
Section: Total Annual Costsmentioning
confidence: 99%